Transarterial Chemoembolization Combined With Lenvatinib Plus PD-1 Inhibitor for Advanced Hepatocellular Carcinoma: A Retrospective Cohort Study - Cai, Mingyue; Huang, Wensou; Huang, Jingjun; Shi, Wenbo; Guo, Yongjian; Liang, Licong; Zhou, Jingwen; Lin, Liteng; Cao, Bihui; Chen, Ye; Zhou, Juan; Zhu, Kangshun (Frontiers in Immunology, 2022)
Purpose: To investigate the efficacy and safety of transarterial chemoembolization (TACE) combined with lenvatinib plus PD-1 inhibitor (TACE-L-P) versus TACE combined with lenvatinib (TACE-L) for patients with advanced hepatocellular carcinoma (HCC). Materials and Methods: Data of advanced HCC patients treated with TACE-L-P (TACE-L-P group) or TACE-L (TACE-L group) from January 2019 to December 2020 were prospectively collected and retrospectively analyzed. The differences in overall survival (OS), progression-free survival (PFS), tumor responses (based on modified Response Evaluation Criteria in Solid Tumors) and adverse events (AEs) were compared between the two groups. Potential factors affecting OS and PFS were determined. Results: A total of 81 patients were included in this study. Among them, 41 received TACE-L-P and 40 received TACE-L. The patients in TACE-L-P group had prolonged OS (median, 16.9 vs. 12.1 months, P=0.009), longer PFS (median, 7.3 vs. 4.0 months, P=0.002) and higher objective response rate (56.1% vs. 32.5%, P=0.033) and disease control rate (85.4% vs. 62.5%, P=0.019) than those in TACE-L group. Multivariate analyses revealed that the treatment option of TACE-L, main portal vein invasion and extrahepatic metastasis were the independent risk factors for OS, while TACE-L and extrahepatic metastasis were the independent risk factors for PFS. In subgroup analyses, a superior survival benefit was achieved with TACE-L-P in patients with extrahepatic metastasis or tumor number >3 but not in those with main portal vein invasion. The incidence and severity of AEs in TACE-L-P group were comparable to those in TACE-L group (any grade, 92.7% vs. 95.0%, P=1.000; grade 3, 36.6% vs. 32.5%, P=0.699). Conclusion: TACE-L-P significantly improved survival over TACE-L with an acceptable safety profile in advanced HCC patients, especially those with extrahepatic metastasis or tumor number >3 but without main portal vein invasion.